Analysis of indoor team sports using video tracking and wireless sensor network - Wilhelm, P.; Monier, E.; Xu, F.; Witkowski, U. (World Congress of Performance Analysis of Sport VIII, 2008)
For the first time it is possible to visualise the actual performance profiles for the players of indoor ball games in training or competition and to apply this knowledge to obtain the optimum training pattern and game strategy. As an enhancement for the sensor network we apply receiver diversity technology for better energy-efficiency and communication reliability, respectively. Our system also provides large flexibility for further designs/improvements, e.g. different heart beat algorithms (QRS Detection) can be implemented on the MCU, the potential to increase the network capacity and the possibility to reduce the packet loss. In the video tracking system template update causes the problem of small template drifting outside the tracked part. To overcome this problem and to reduce the number of manual corrections we are enhancing the tracking by making use of colour information.